Towards Inclusion through Awareness of Sexual Harassment Policies Case of Teacher Education Institution - Senapati, Bhabani; I.P., Gowramma (JOURNAL OF INDIAN EDUCATION, 2022)
Educational institutions are vested with the responsibility of offering a safe, secure, and inclusive teaching-learning environment. There are many instances showing that real inclusion in terms of gender, disability, sexuality, race, and ethnicity is always ignored at all levels of education. The paper aimed to explore the status of legal awareness on sexual harassment and raise the level of sensitivity towards inclusion among students of the teacher education institution of Odisha. The research found that 90 per cent of respondents are unaware of the Internal Complaint Committee (ICC) for handling sexual harassment cases, its composition, procedures for grievances, and its functions. 14 per cent of respondents have received awareness training programmes on gender equality and women’s issues but not on sexual harassment. It is recommended to create and update policies related to sexual harassment and communicate it in various ways in the institution to raise the awareness level among students in teacher education institutions ensuring a safe learning environment.